Identification of Axial Compressor Dynamics using Tabu Search Optimization. Issue 28 (2015) - Schoen, Marco P.; Lee, Ji-Chao; Lin, Feng
Abstract: Identification of a one stage axial compressor system is addressed using existing and a newly proposed approach that incorporates a priori knowledge of the system into the identification algorithm. The optimization of the proposed cost functions is accomplished by utilizing a Tabu Search algorithm. In addition to the identification of the compressor dynamics, a new measure for the flow state in the blade passage is proposed. The identification of the dynamics within the blade passage and the proposed flow measure allow for the inspection of the limits for the utilized actuation.